A new mysid (Crustacea, Mysida) from the Ladinian Stage (Middle Triassic) of Conca de Barberà (Catalonia, NE Iberian Peninsula). (17th July 2017) - San Vicente, Carlos; Cartanyà, Joan
Abstract: The oldest known fossil mysid (order Mysida) Aviamysis pinetellensis n. gen. n. sp. is described here from two nearly complete specimens found in the Alcover unit from El Pinetell (Catalonia). It differs significantly from other Mysida and is placed in a new genus assigned to the family Mysidae and tentatively to the subfamily Boreomysinae. These specimens represent the first described mysid material from the Alcover outcrops (Middle Triassic, upper Ladinian, 235–242 Ma), extending the known geological range of the poorly understood fossil fauna of the order Mysida by at least 70 Myr.